COMPARISON OF JENKINS AND GITLAB CI/CD TO IMPROVE DELIVERY TIME OF BASU DAIRY FARM ADMIN WEBSITE - Kuncara, Alif Babrizq; Kusumo, Dana Sulistyo; Adrian, Monterico (Informatika, Universitas Jenderal Soedirman, 2024)
The Basu Dairy Farm admin website is a web-based information system developed using monolithic architecture. The delivery process of source code changes from the GitLab repository on the